From Planar to Cage in 15 Easy Steps: Resolving the C60H21F9- → C60- Transformation by Ion Mobility Mass Spectrometry - Greisch, Jean-Francois; Amsharov, Konstantin; Weippert, Juergen; Weis, Patrick; Boettcher, Artur; Kappes, Manfred M. (Journal of the American Chemical Society, 2016)
A combination of mass spectrometry, collision-induced dissociation, ion mobility mass spectrometry (IM-MS), and density functional theory (DFT) has been used to study the evolution of anionic species generated by laser-desorption of the near-planar, fluorinated polycyclic aromatic hydrocarbon (PAH), C60H21F9 (s). The dominant decay process for isolated, thermally activated C60H21F9- species comprises a sequence of multiple regioselective cyclodehydrofluorination and cyclodehydrogenation reactions (eliminating HF and H2, respectively, while forming additional pentagons and/or hexagons). The DFT calculations allow us to set narrow bounds on the structures of the resulting fragment ions by fitting structural models to experimentally determined collision cross sections. These show that the transformation of the precursor anion proceeds via a series of intermediate structures characterized by increasing curvature, ultimately leading to the closed-shell fullerene cage C60- as preprogrammed by the precursor structure.
CRIS-Team Scopus Importer:2023-03-20